Iot-Based Smart Trash Monitoring Using Blynk Application - Widodo; Ali Nur Rifky (BEST, 2021)
Poor waste management and lack of public awareness of environmental hygiene, especially if waste is disposed of in the local trash can, causes garbage to accumulate and emit bad odors which can be a source of disease transmission. The lack of information technology for waste management by janitors can cause slow waste disposal. Based on these problems, it is necessary to equip an automatic trash can with a monitoring function in real time. Added the IOT (Internet of Things) function, which can provide initial information indicating that the trash can is full and can be quickly picked up by the garbage collector. The smart trash can prototype uses an ESP 32 microcontroller as a system control. Servo to control the trash can cover. The output of DF Player is in the form of thanks to people who throw garbage in its place. Ultrasonic sensors can detect human presence and waste volume and send monitoring results in real time as well as notifications to the blynk application as a notification if the trash can is full.